Correlates of nicotine dependence in men with childhood attention-deficit/hyperactivity disorder: a 33-year follow-up - García Murillo, Lourdes; Ramos-Olazagasti, María A.; Klein, Rachel G.; Mannuzza, Salvatore; Castellanos, Francisco Xavier (Attention deficit and hyperactivity disorders, 2019)
Identify correlates of nicotine dependence [lifetime (l) and ongoing (o)] in adults with attention-deficit/hyperactivity disorder (ADHD) in childhood. We conducted a 33-year prospective follow-up of boys (mean age 8) with combined type ADHD ( n = 135/207, 65% original sample). Correlates of nicotine dependence in adulthood were selected from characteristics obtained in childhood and adolescence. Among selected childhood features, only immature behavior was significantly related to nicotine dependence (OR (o) = 0.29, p = 0.02), indexing decreased risk. In contrast, several adolescent variables significantly correlated ( p < 0.01) with nicotine dependence at mean age 41, including alcohol substance use disorder (SUD, OR (l) = 4.97), non-alcohol SUD (OR (o) = 4.33/OR (l) = 10.93), parental antisocial personality disorder (OR (l) = 4.42), parental SUD (OR (l) = 3.58), dropped out of school (OR (l) = 2.29), impulsivity (OR (o) = 1.53/OR (l) = 1.59), hyperactivity (OR (o) = 1.38), and number of antisocial behaviors (OR (o) = 1.10/OR (l) = 1.14). Results highlight the role of adolescent psychopathology in the development of nicotine dependence, motivating prospective longitudinal efforts to better define the developmental trajectories of risk and protection.